2014
DOI: 10.1136/bjsports-2014-093702
|View full text |Cite
|
Sign up to set email alerts
|

Reduced glenohumeral rotation, external rotation weakness and scapular dyskinesis are risk factors for shoulder injuries among elite male handball players: a prospective cohort study

Abstract: Injury prevention programmes should incorporate interventions aimed at improving glenohumeral rotational range of motion, external rotation strength and scapular control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
287
12
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(331 citation statements)
references
References 41 publications
17
287
12
15
Order By: Relevance
“…12,32 Clarsen et al 9 reported that decreased total ROM was related to increased shoulder pain in handball players.…”
Section: Glenohumeral-rotation Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,32 Clarsen et al 9 reported that decreased total ROM was related to increased shoulder pain in handball players.…”
Section: Glenohumeral-rotation Motionmentioning
confidence: 99%
“…9,11 Reduced shoulder IR is defined as a glenohumeral IR deficit (GIRD). 12 Individuals with more than 188 of IR ROM loss and 58 difference in total-rotation ROM between the dominant and nondominant shoulders are at risk for shoulder injury.…”
Section: à11mentioning
confidence: 99%
“…Results indicate that for a population of adolescent athletes with an amateur sports level, the dyskinesis prevalence is high; however, it is not associated with pain and does not seem to affect measures of upper limb function. Although some studies support the relationship between pain/ lesion and scapular dyskinesis 2,[7][8][9][10][11] , more than half of the current sample (56.7%) presented changes in scapular movement without, however, being associated with shoulder pain. The results of this study corroborate those of Oliveira et al 28 who analyzed amateur male athletes with shoulder injury syndrome and observed no association between dyskinesis and shoulder pain.…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, the modification in the scapula positioning, called scapular dyskinesis, has been studied because it presents possible relations with the presence of pain and shoulder injuries in athletes 2,[6][7][8] . Most of the studies state the relation between shoulder pain/ injury and scapular dyskinesis 2,7,[9][10][11] . Such research ensures that ORIGINAL ARTICLE DOI 10.5935/2595-0118.20180009 changes in scapular kinematics may result in structural and functional changes in the glenohumeral and acromioclavicular joints, decreased subacromial space, changes in the scapular muscles activation and, consequently, leading to dysfunctions such as shoulder-rotator cuff syndrome, rotator cuff tendinopathies, glenohumeral instability, and other conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder pain is a common injury in elite handball players with the average weekly prevalence being approximately 28% during the season (Clarsen, Bahr, Andersson, Munk, & Myklebust, 2014). This condition is also highly prevalent in other throwing and overhead sports such as baseball (Amin et al, 2015).…”
Section: Commentarymentioning
confidence: 99%